Pengaruh Kualitas Komite Audit dan Kualitas Audit Terhadap Kualitas Pelaporan Keuangan Perusahaan - Permatalia, Riska; Haryono, Slamet (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2021)
Users of financial statements need the quality of financial reporting to ensure the sustainability of the company, but not a few commit fraud. So we need an audit committee and audit quality for the big four/nonbig four. This study uses panel data for 2014-2019 from manufacturing companies registered with JII and data sourced from annual reports and company financial statements. As a result, the independent variable is explained by the audit committee's accounting expertise and audit quality has a positive and significant effect on 5% and the number of audit committee meetings is significant at 10% on the quality of financial reporting, while the variable number of audit committee members and size has no significant negative effect and leverage. positive and insignificant effect on the quality of financial reporting.